Retinal microvasculature features in patients with migraine: a systematic review and meta-analysis - Pang, Yulian; Cao, Ting; Zhang, Qinglin; Hu, Haijian; Wang, Zhiruo; Nie, Jiahe; Jin, Ming; Chen, Guiping; Zhang, Xu (Frontiers in Neurology, 2023)
Background Migraine is a central nervous system disorder involving neuronal and vascular factors. The brain has a close anatomical relationship with retinal vessels and similar regulatory processes, and the retinal vascular system is the only in vivo vessel that can be directly visualized, while optical coherence tomography angiography (OCTA) is an advanced retinal vascular imaging technique. In this study, OCTA was used to study the retinal vascular density (VD) and foveal avascular zone (FAZ) in migraine patients, which provided a theoretical basis for its use as a candidate for rapid and non-invasive diagnosis of migraine. Methods Published studies comparing retinal microvascular profiles between migraine patients and healthy controls were obtained by a comprehensive search of electronic databases. Nine studies were finally included, including 775 eyes (migraine group: 444 eyes, control group: 331 eyes). Pooled effect sizes were presented as standardized mean differences (SMDs) and 95% confidence intervals (CIs). Statistical analysis was performed using Review Manager software (version 5.30). Results The combined results revealed that the superficial and deep macular whole enface VD (MWEVD) (superficial VD: SMD = −0.30, P = 0.0001; deep VD: SMD = −0.61, P = 0.02), superficial foveal VD (FVD) (SMD = −0.42, P = 0.03), deep parafoveal VD (PFVD) (SMD = −0.31, P = 0.002), and peripapillary VD (PVD) (SMD = −0.49, P = 0.002) were significantly reduced in migraine patients compared with healthy people. However, there was a significant increase in the area of the FAZ in migraine patients (SMD = 0.56, P < 0.0001). Conclusion Migraine patients are prone to retinal microcirculation disorders, such as decreased blood vessel density and increased avascular area in the fovea. This provides a theoretical basis for OCTA as a candidate for rapid, non-invasive diagnosis of migraine.